Properties of the plant- and manure-derived biochars and their sorption of dibutyl phthalate and phenanthrene - Qiu, Mengyi (Nature Publishing Group, 2014)
The properties of plant residue-derived biochars (PLABs) and animal waste-derived biochars (ANIBs) obtained at low and high heating treatment temperatures (300 and 450°C) as well as their sorption of dibutyl phthalate (DBP) and phenanthrene (PHE) were investigated in this study. The higher C content of PLABs could explain that CO(2)-surface area (CO(2)-SA) of PLABs was remarkably high relative to ANIBs. OC and aromatic C were two key factors influencing the CO(2)-SA of the biochars. Much higher surface C content of the ANIBs than bulk C likely explained that the ANIBs exhibited higher sorption of DBP and PHE compared to the PLABs. H-bonding should govern the adsorption of DBP by most of the tested biochars and π-π interaction play an important role in the adsorption of PHE by biochars. High CO(2)-SA (>200 m(2) g(−1)) demonstrated that abundant nanopores of OC existed within the biochars obtained 450°C (HTBs), which likely result in high and nonlinear sorption of PHE by HTBs.